The Neurostructure of Morality and the Hubris of Memory Manipulation - DePergola II, Peter A. (The new bioethics, 2018)
Neurotechnologies that promise to dampen (via pharmacologicals), disassociate (via electro-convulsive therapy), erase (via deep brain stimulation), and replace (via false memory creation) unsavory episodic memories are no longer the subject of science fiction. They have already arrived, and their funding suggests that they will not disappear anytime soon. In light of their emergence, this essay examines the neurostructure of normative morality to clarify that memory manipulation, which promises to take away that which is bad in human experience, also removes that which enables human beings to be good. Concepts such as free will, moral responsibility, and the neurobiological basis of moral reasoning are explored to underscore the fundamental hubris inherent to the memory manipulation enterprise.